DrugEx: Deep Learning Models and Tools for Exploration of Drug-Like Chemical Space - Šícho, Martin; Luukkonen, Sohvi; van den Maagdenberg, Helle W; Schoenmaker, Linde; Béquignon, Olivier J M; van Westen, Gerard J P (Journal of chemical information and modeling, 2023)
The discovery of novel molecules with desirable properties is a classic challenge in medicinal chemistry. With the recent advancements of machine learning, there has been a surge of de novo drug design tools. However, few resources exist that are user-friendly as well as easily customizable. In this application note, we present the new versatile open-source software package DrugEx for multiobjective reinforcement learning. This package contains the consolidated and redesigned scripts from the prior DrugEx papers including multiple generator architectures, a variety of scoring tools, and multiobjective optimization methods. It has a flexible application programming interface and can readily be used via the command line interface or the graphical user interface GenUI. The DrugEx package is publicly available at https://github.com/CDDLeiden/DrugEx.
Keywords: Deep Learning; Software; Drug Design; software; deep learning; Machine Learning; strojové učení; racionální návrh léčiv